PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN KONSTRUKTIVISME UNTUK PENCEGAHAN KEBAKARAN LAHAN DAN HUTAN (KARLAHUT) PADA PEMBELAJARAN IPA KELAS VII SMP - Fitri Andriani; Yustina '; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Land and forest fire has occurred for more than 18 years in Indonesia, especially in Riau, it show that preventing and addressing land and forest fire needs to be done in various aspects of life, one of which is education, we have to impart knowledge about land and forest fire to students. This research is expected to increase the understanding and knowledge of students about land and forest fire and peat swamp ecosystem, so in the future the students can perform preventive action against land and forest fire problems. This research was conducted at the Laboratory PMIPA of Biology Department of the University of Riau and SMPN 1 Tambang in February until April 2016. This type of research is the development with ADDIE’s model of integration to the stage of development. There are 4 LKPD developed. Instruments of data collection in this study is the assessment sheet / validation LKPD and student questionnaire responses. After LKPD developed, validated by 4 validator and then do the first test at 16-22 student in the 4th semester of biology education FKIP UR, and the second test at 18 students of Class VII at SMPN 1 Tambang. The results of the validation LKPD 1 shows the mean score 3,16 is valid category, LKPD 2 with a mean score of 3,29 is very valid category, LKPD 3 with a mean score of 3,29 is very valid and LKPD 4 with a score of 3,27 is very valid category. The results of the questionnaire responses in the first test showed a mean score of 91 with very good categories and the results of questionnaires in the second test showed a mean score of 89 with very good category. It can be concluded that LKPD Based constructivist approach to prevention the land and forest fire could provide insight and knowledge about land and forest fire and peat swamp ecosystems in particular as well as fit for use in science teaching in schools.Keywords: development, LKPD, Constructivism, land and Forest Fires